Perspectives on international financial reporting and auditing in the airline industry - Öztürk, Can (Studies in managerial and financial accounting ;, 2022)
Perspectives on International Financial Reporting and Auditing in the Airline Industry draws on the framework of financial reporting in the global airline industry for the year 2018 and focuses on the airline financial reporting based on International Financial Reporting Standards (IFRSs) and audit of airline financial reporting based on International Standards on Auditing (ISAs). Contributing to the accounting policy choice debate from a sector-specific perspective, this book considers the existing policy choices under IFRSs, in order to observe the diversity, and comparability in the airline industry. It analyses the cumulative of effect of the adoption of IFRS 15 Revenue from Contracts with Customers and IFRS 16 Leases in the airline industry, including the case of Air France - KLM and it takes a picture of segment reporting in terms of diversity and comparability in the airline industry. Finally, it analyzes audit reports of airlines reporting under IFRS in terms of International Standards on Auditing, in terms of diversity of audit practices. This book provides valuable insights into perspectives on international financial reporting and auditing in the airline industry and is essential reading for both researchers and professionals.